Note on bean yellow mosaic virus naturally infecting Phaseolus vulgaris L. in Spain - De Blas, C.=700 1 Carazo, G.; Saiz, M.; Romero, J.; Castro, S.
(Es, En)
ilus., 10 ref.
Keywords: POTYVIRUS MOSAICO AMARILLO FRIJOL; SINTOMAS; HUESPEDES; ESPAÑA; JUDIA